2015
DOI: 10.1080/00071668.2015.1016478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rearing systems on muscle and meat quality traits of slow- and medium-growing male chickens

Abstract: 1. This experiment was conducted to evaluate the effect of production system on the meat quality of slow- and medium-growing chickens. A total of 1075 1-d-old male chicks were equally divided into 6 experimental groups, represented by three strains (SG: TETRA-H, MG1: TETRA HB Color, MG2: Shaver Farm) and were reared in a poultry house in floor pens (12 males/m(2)). 2. On d 49, 150 healthy birds (50/genotype) were placed in a free-range family farm while the rest of the birds remained indoors. All birds were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
6
15
2
1
Order By: Relevance
“…Indeed, the breast meat of IN chickens had both a lower pH and a higher drip loss than that of the AS chickens. Similar differences in pH between indoor and outdoor chickens were obtained by Ponte et al (2008b), Jiang et al (2011), andAlmasi et al (2015). Muscle fiber density and size may have been affected by free-range access, which could have altered the post mortem pH decline (Jiang et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the breast meat of IN chickens had both a lower pH and a higher drip loss than that of the AS chickens. Similar differences in pH between indoor and outdoor chickens were obtained by Ponte et al (2008b), Jiang et al (2011), andAlmasi et al (2015). Muscle fiber density and size may have been affected by free-range access, which could have altered the post mortem pH decline (Jiang et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…Free-range chickens reached 96% and 97% of the indoor chickens' BW. These results agree with Almasi et al (2015); however, Sales (2014) did not observe significant variability in BW between indoor and free-range systems. The stocking density did not affect the final BW.…”
Section: Resultssupporting
confidence: 82%
“…The results correspond with the findings of Almasi et al (2015) but are in contrast with the data of Funaro et al (2014), Sales (2014), and Skrivan et al (2015), who found higher meat yellowness in (Funaro et al 2014). The variability in meat colour could also be explained by the length of the experiment and the free-range period (Sales 2014), which was 27 days in this experiment and much shorter than in the studies of Funaro et al (2014) and Almasi et al (2015). The breast muscle shear force was significantly lower in free-range chickens without the effect of stocking density (Table 3).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is 178 g more than in the same genotype in the present experiment. In the case of dual-purpose lines, male Tetra-H chicks from indoor and free-range housing systems weighed 1790 g after 70 days of fattening [33] and Bresse Gauloise raised under a welfare-enhanced organic system that includes access to pasture weighed 2570 g after 84 days [34]. The feed conversion of Dominant Sussex D 104 cockerels (0-84 days) in the study of Jelínková [32] was 3.1.…”
Section: Discussionmentioning
confidence: 99%